Design and performance analysis of 28 GHz two-port MIMO rectangular microstrip patch antenna array for 5G applications - Ismam, Shafiul; Hossain, Delwar; Salam, Syed Munimus; Rashid, Muhammad Mahbubur (AlamBiblio Publishers, 2023)
A rectangular microstrip patch antenna array with two ports, designed for operation in the mm-wave band at 28 GHz for 5G applications, has been developed to exhibit superior gain and efficiency. This paper introduces a 12-element array activated by a feed network utilizing a T-junction power combiner/divider. The array elements consist of rectangular patch antennas inserted throughout the structure. The designed array antenna exhibited a measured impedance bandwidth of 1.42 GHz. The simulated findings indicate that the antenna achieved a favorable impedance match, with isolation levels below -22 dB throughout the frequency range. The whole substrate board dimensions were 19.99 × 26.968 × 0.254 mm3. The array is positioned on the substrate material known as Rogers RT5880, resulting in a consistent and reliable radiation pattern. The CST MWS software is employed to model and simulate the microstrip patch array antenna. CST MWS is an electromagnetic simulator utilizing the Finite Integration in Technique (FIT) methodology to model and analyze full-wave electromagnetic phenomena accurately. The realized gain of 15 dBi has been reached for the combined array, whereas the individual arrays have a realized gain of 12.3 dBi. The calculated overall efficiency is roughly -0.5 decibels. The antenna array under consideration has demonstrated favorable multiple-input multiple-output (MIMO) capabilities, as evidenced by an envelope correlation coefficient (ECC) of less than 0.1.